Hidden Deficiency: How Metformin Use Drives Vitamin B12 Depletion in Type 2 Diabetes - Rizwan Ali Talpur; Shahzad Ali Jiskani; Muhammad Ishaque Bhatti; Anam Shaikh; Jawed Iqbal; Rida Qureshi (Liaquat National Journal of Primary Care, 2025)
Background: Type 2 diabetes mellitus (T2DM) is commonly managed with metformin, an effective oral hypoglycemic agent. However, prolonged metformin use has been linked to vitamin B12 deficiency, a condition that, if left untreated, can lead to serious complications. Limited research on this issue in certain populations underscores the importance of understanding metformin’s impact on vitamin B12 levels. Objective: The study aims to assess the prevalence of vitamin B12 deficiency in T2DM patients on long-term metformin therapy and to identify its associated factors. Methodology: A cross-sectional study was conducted at Chandka Medical College, Larkana for one year (January 2023 to December 2023) with 200 T2DM patients treated with metformin for one year. Participants were interviewed regarding sociodemographics, lifestyle, and clinical history, with particular attention to metformin dose and treatment duration. Blood samples were collected to measure serum vitamin B12 levels, and data was analyzed using SPSS 24.0. A p-value of ≤0.05 was considered statistically significant. Results: The mean age of participants was 43.75 years, with an age distribution consisting of 41-50 years (42.5%), followed by 31- 40 years (35%). The majority of patients were females (56%). The prevalence of vitamin B12 deficiency was 40%. In multivariable regression analysis, female gender (aOR=1.82, 95% CI: 1.10-3.05) and increasing diabetes duration (aOR=2.08, 955 CI: 1.20-3.45) were found to be associated with b12 deficiency. No significant relationship of B12 deficiency was found with metformin dosage or duration. Conclusion: This study highlights a substantial prevalence of vitamin B12 deficiency among T2DM patients on metformin, with female gender and longer diabetes duration identified as a notable risk factor. Regular monitoring of vitamin B12 levels in metformintreated patients, particularly females and those with prolonged diabetes, is recommended to prevent potential complications